Weak low-frequency electromagnetic oscillations in water. (3rd April 2017) - Liboff, A. R.; Poggi, Claudio; Pratesi, Piero
ABSTRACT: Recent observations of low-frequency electromagnetic oscillations in water suggest an inductive structural component. Accordingly, we assume a helical basis enabling us to model water as an LC tuned oscillator. A proposed tetrahedral structure consisting of three water molecules and one hydronium ion is incorporated into the Boerdijk–Coxeter tetrahelix to form long water chains that are shown to have resonance frequencies consistent with observation. This model also serves to explain separately reported claims of ion cyclotron resonance of hydronium ions, in that the tetrahelix provides a built-in path for helical proton-hopping.